Temporary Thyroid Dysfunction and Catecholamine Excess Due to Mercury Poisoning in 6 Cases - Yavuz Özer; Mehmet Yıldız; Hande Turan; Aydilek Dağdeviren Çakır; Gürkan Tarçın; Dilek Bingöl Aydın; Elvan Bayramoğlu; Fatih Haşlak; Sezgin Şahin; Amra Adrovic; Kenan Barut; Olcay Evliyaoğlu; et al. (Turkish Archives of Pediatrics)
Objective: Mercury poisoning is a condition with multiple-organ dysfunction that has effects on the central nervous system, gastrointestinal system, cardiovascular system, skin, lungs, and kidneys. It can be fatal or may result in sequelae such as neurological disturbances, if treated late or left untreated. The endocrinological effects of mercury exposure are not well-known. We aimed to evaluate patients with mercury poisoning.